Being Christian through External Giving - Cheung, Steve Wai Lung (Religions, 2019)
This study examines how Christian informants understand and practice external (charitable) giving outside of their church, both in terms of money and volunteering time and effort. While existing quantitative researches have informed us primarily about the determinants of giving in the West, we carry out a small case study in a church in an Asian city of Hong Kong to explore how local Christians understand and practice external giving. It is found that external giving is not just an obligatory religious code of conduct that the Christians are obliged to follow. More essentially, drawing reference from the concept of technology of the self, we argue that giving is an integral part of the making of the Christian self. Through giving, individual Christians redefine, transform, and enact their sacred selves in relation to God and others in the community of the faithful. At a collective level, external giving contributes to the construction of a sacred moral economy, which places Christian givers and the needy recipients in a transcendent social relationship. In this state of transcendent social relationship, the givers and recipients are all children of God, hence of equal status. As such, the secular social distinction and material hierarchy distinction between these two groups pales into insignificance. Furthermore, we argue that while secular considerations of economic rationality colour how Christians select the recipients of their giving, these practical concerns are also spiritualized and incorporated into their logic of Christian morality.